MANAJEMEN PEMENUHAN KEBUTUHAN ANAK DI KELUARGA DALAM PERSPEKTIF GENDER - Syaiful Marwan; Himyar Pasrizal (AGENDA: Jurnal Analisis Gender dan Agama, 2019)
Every family member has different needs from one another. Children are the most important members of the family, especially in completing their needs. Each child has different basic needs. In the case of gender, sometimes boys are often prioritized over girls. But on the other hand girls also have many needs related to their nature as women. This various cases cause different need compliance that requires parents’ consideration. Therefore, parents need to accommodate their children needs which have gender diversity. In managing these children's needs, parents' creativity and understanding of their children are needed.